Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Pegawai Puskesmas Cinta Maju Kecamatan Belangpegayon - Dewi, Jasniar Pita; Supriadi, Supriadi; Nasution, Ismail (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This study aims to determine whether leadership style and compensation significantly influence the performance of employees at the Cinta Maju Community Health Center in the Belangpegayon District. This research is of the associative type, with the population of the study being all employees of the Cinta Maju Community Health Center in the Belangpegayon District, totaling 40 employees. The sample used is saturated sampling, meaning all 40 individuals in the population are taken as samples. The data analysis technique used is multiple linear regression analysis. Based on hypothesis testing, the results of this study are as follows: leadership style influences employee performance, compensation influences employee performance, and leadership style and compensation together influence employee performance